Legal Culture, Perspective Reproductions, and the Thai Legal Professionals - Na Pomphet, Boonchoo (CMU Journal of Law and Social Sciences, 2018)
Legal professionals, in particular judges at the Court of Justice and the Constitutional Court, have lately received some marked criticisms targeting their perspective, paradigm, and legal culture. The dimension of judicial decisions has expanded to include political, economic, and social aspects. Community rights and political cases have been introduced to the Court in a more visible manner. Yet, the Court steadfastly refuses to take these new dimensions into consideration and focuses solely on the letter of the statute when rendering justice. Consequently, the general public outcry can be easily observed, but few seeks to understand the underlying legal culture of legal professionals. Drawing from well-researched empirical evidence, this article argues that the origin of Thailand’s legal culture stemmed from the legal education. The process of education proceeds to shape not only the knowledge but also the perspective of legal professionals. This shared perspective is often manifested in the form of judicial decisions which rigidly adhere to the traditional approach and neglect the economic, social, and political context. These decisions are then studied and replicated in future decisions thus reproducing the legal perspective forming the foundation of Thailand legal culture. The article concludes with a hopeful perspective in the near future.